The Use of Ozenoxacin in Pediatric Patients: Clinical Evidence, Efficacy and Safety - Davino, Giusy; D’Alvano, Tiziana; Esposito, Susanna (Frontiers in Pharmacology, 2020)
Impetigo is the most common childhood skin infection in the world. There are two presentations of impetigo: nonbullous (or impetigo contagiosa) and bullous. The nonbullous type is caused by Staphylococcus aureus and group A beta-haemolytic Streptococcus and occurs in 70% of impetigo cases. Impetigo is usually a self-limited condition, but complications can sometimes occur. Treatment options depend on the extent and site of the lesions and on the presence of systemic symptoms. The increase in multidrug resistance pathogens, such as methicillin-resistant Staphylococcus aureus (MRSA), mupirocin-resistant Staphylococcus aureus (MupRSA) or quinolone-resistant Staphylococcus aureus (QRSA), requires the development of new antibiotics against these agents. The aim of this review is to analyse the efficacy and safety of ozenoxacin in paediatric patients compared to those of other approved topical antimicrobial therapies. The bactericidal activity against both susceptible and resistant organisms is an important feature of ozenoxacin because the bacterial strain and potential for resistance are generally not known at the beginning of therapy. Additionally, its minimal dermal absorption and its capability to reach high concentrations in the upper layers of the epidermidis agrees with the current principles aimed at avoiding the emergence of bacterial resistance in presence of a good safety profile. Further studies with real-life analyses and pharmacoeconomic evaluation are needed to confirm its role as first-line and second-line therapy in children with impetigo.